To tell or not to tell: a systematic review of literatures on confidentiality and disclosure concerns across scholarly disciplines - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Confidentiality and disclosure remain a significant concern regardless of age, gender, race, religion, national origin, and social class. Confidentiality reflects the act of keeping secret and protecting the privacy of clients. On the other hand, disclosure reflects the act of sharing matters with others. The thoughts about ‘to tell or not to tell’ exists in every individual especially when the individual share issues with the other person. Some choose to disclose and some choose to restrict disclosure. Thus, the aim of this systematic review is to discuss various concerns about confidentiality and disclosure across multiple scholarly disciplines. Furthermore, the review would provide comparisons between the need to protect confidentiality and the need to disclose. An electronic database was used to retrieve comprehensive literature. A number of articles were evaluated and the review involved multiple disciplines. The methodology began with the designation of a search strategy, data filtration, in-depth filtration involving inclusion and exclusion criteria, and production of final output. We conclude that most of the findings highlights the need to protect clients’ confidentiality and control disclosure whereas the rest of the findings discussed the need for disclosure. In short, the review highlights that confidentiality is an ethical duty. The inclusion of multiple scholarly disciplines is to show the widespread of counseling in various fields and therefore, it is necessary to pay additional attention to ensure all the fields provide assurance of confidentiality. All counseling practitioners, social workers, and legal and mental health practitioners are obligated to protect clients’ information from disclosure; unless authorized by clients or when they noticed confirmed sign of danger. Confidentiality would be the highest preference expected by clients and it is the duty of practitioners to safeguard them. We argue that confidentiality should remain as a significant and utmost concern. In contrast, disclosure should remain restrained.